2015
DOI: 10.1111/ppl.12362
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical plasticity of Lepidium latifolium as ‘sleeper weed’ in Western Himalayas

Abstract: To understand the spread of native populations of Lepidium latifolium growing in different altitudes in Ladakh region of Western Himalayas, photosynthetic and fluorescence characteristics were evaluated in relation to their micro-environment. Three sites representing sparsely populated (SPS), moderately populated (MPS) and densely populated site (DPS) were selected. Results showed that the DPS had higher photosynthetic accumulation than MPS and SPS. The higher transpiration rate at DPS despite lower vapor pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In each of these processes, metabolite profiles can be used to measure plant responses with different biochemical resolution [ 112 ]. They can also be used to identify biochemical traits that can serve as marker, e.g., for phenotypic plasticity, chemical interactions with other organisms or resolving the invasive potential of exotic plants [ 37 , 47 , 110 ]. Thus, Eco-Metabolomics is a discipline which allows researchers to describe interactions between processes acting at different spatiotemporal scales.…”
Section: Bridging the Gap Between Biochemistry And Ecologymentioning
confidence: 99%
“…In each of these processes, metabolite profiles can be used to measure plant responses with different biochemical resolution [ 112 ]. They can also be used to identify biochemical traits that can serve as marker, e.g., for phenotypic plasticity, chemical interactions with other organisms or resolving the invasive potential of exotic plants [ 37 , 47 , 110 ]. Thus, Eco-Metabolomics is a discipline which allows researchers to describe interactions between processes acting at different spatiotemporal scales.…”
Section: Bridging the Gap Between Biochemistry And Ecologymentioning
confidence: 99%
“…Chlorophyll fluorescence was measured on fully expanded leaves using a portable photosynthesis system (LI-6400, LI-COR, Lincoln, NE, USA) equipped with a fluorescence chamber (LI-6400-40) with modifications as in Bhat et al [29]. ΦPSII was determined as Fm -Fs/Fm , maximal efficiency of PSII by using Fv/Fm and intrinsic efficiency of PS II was by using Fv/Fm as suggested by Maxwell and Johnson [43].…”
Section: Chlorophyll a Fluorescence Measurementsmentioning
confidence: 99%
“…Thus, proline metabolism may be considered as a key tool for protecting photosynthesis and increasing tolerance against stress conditions. Glutathione is known in signaling pathways that facilitate the acclimation of chloroplast processes to highlight and abiotic stress in order to increase yield and stress tolerance under changing environments [27][28][29][30]. Studies have shown that the detoxifying compounds such as reduced glutathione (GSH), proline and phenolics provide tolerance under changing environments [14,21,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Lepidium latifolium (perennial pepperweed) is an ecologically important plant belonging to the family Brassicaceae. Although native to southern Europe and Asia (Bhat et al 2016, Schultze‐Motel 1986), it has shown widespread presence in most parts of the world, including the western United States, coastal New England, Mexico, Canada, and Australia (Young et al 1995). The wide ecological amplitude of Lepidium latifolium suggests that it is a reservoir of several novel physiological and biochemical mechanisms that help this plant to adapt to a diverse set of environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown a responsive redox mechanism where the glutathione plays an important role in the induction of antioxidant enzymes having higher thiol content (Kaur, Bhat, et al 2013). Dynamic photosynthetic machinery to mitigate higher photosynthetic efficiency and light‐dependent xanthophyll cycle turnover has also been shown to suggest the wider adaptability of this plant in the Himalayas (Bhat et al 2016). Lepidium latifolium has also been recognized as the highest source of sinigrin having nutraceutical importance (Kaur, Hussain, et al 2013).…”
Section: Introductionmentioning
confidence: 99%